Clinical utility of multielectrode contact mapping for scar‐related ventricular tachycardia ablation: A prospective single‐center experience. Issue 4 (6th June 2014) - Nakahara, Shiro; Hori, Yuichi; Kamijima, Tohru; Tsukada, Naofumi; Nishiyama, Naoki; Yamada, Kohta; Hayashi, Akiko; Komatsu, Takaaki; Kobayashi, Sayuki; Sakai, Yoshihiko; Taguchi, Isao; Takayanagi, Kan
Abstract: Background: As with the use of circular catheters for pulmonary vein antral ablation, it may be favorable to use multipolar catheters for substrate mapping of the left ventricle (LV). The purpose of this study was to investigate the clinical feasibility of using multielectrode mapping combined with an impedance‐based electroanatomic mapping system for scar‐mediated ventricular tachycardia (VT). Methods: By using the multielectrode catheter in conjunction with the Velocity system, we obtained both geometric and electrogram data simultaneously, through transseptal and transsubxiphoid approaches. Higher‐density mapping was performed in areas of dense scar (<0.5 mV) and border zones (0.5–1.5 mV). All late potentials (LPs) observed on the multipoles were tagged, and pace mapping was performed at those sites for comparison with the targeted VT morphology. Ablation was performed at target sites on the multipolar catheter that were identified by pace mapping, as well as at sites identified to have LPs and to be the origin of the premature ventricular complexes (PVCs) that triggered the VT. Results: Sixteen patients (8/8: ischemic/nonischemic cardiomyopathy) underwent endocardial ( n =16) and epicardial ( n =8) mapping. The mean number of endocardial and epicardial mapping points was 504±136 and 670±211, respectively, with an average mapping time of 21±6 min. LPs were seen in 13 patients (81%), and good (56%) and perfect (31%) pace maps were seen in 14 patients (88%). In two patients, sites with the earliest activation of PVCs that triggered VT were successfully identified with multipolar catheter mapping. A distinct geometric distortion of the endocardial LV was confirmed in two patients, and those were modified by dividing the LV into two chambers. After 10.0±3.7 months, 71% of the patients have remained free of VT episodes. Conclusion: Multipolar catheter mapping combined with the Velocity system results in a high‐density delineation of the LV substrates in a relatively short time, suggesting that this is a feasible alternative mapping strategy for scar‐related VT.